Upaya Peningkatan Pengetahuan Orangtua Balita Melalui Edukasi Flu Singapura - siwi, ignasia (ABDIMAS Madani, 2022)
Singapore flu is an infectious disease that is very easy to spread, especially in schools and occurs in toddlers. Based on the request of KB and TPA Bunayya ICBB, to help the problem of Singapore flu suffered by toddlers, community service was conducted by giving counseling and presentation. The service aimed to increase the knowledge of parents of toddlers about the Singapore flu. The participants of this activity were parents of children under five at the KB and TPA Bunayya ICBB as many as 22 people. The method is the empowerment of parents and the school, namely problem assessment, solution planning, implementation to evaluation involving parents and the school. This activity was carried out for 1 month from May 24 – June 27, 2022. The results of the activity found that the average score before education was 76 and the average score after education was 100. Based on the results of the activity, it can be concluded that Singapore flu education can increase the knowledge of parents of toddlers.